Manajemen Blended Learning Mata Pelajaran Akidah Akhlak pada Masa Pandemi - Sitam Sitam (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2021)
MI Ma'arif NU 02 Karangpakis, Nusawungu District, Cilacap Regency, during the Covid 19 pandemic, applied a blended learning model to learning the Akidah Akhlak subject. The formulation of the problem, first is how to plan blended learning for the Akidah Akhlak subject at MI Ma'arif NU 02 Karangpakis, secondly how is the implementation of blended learning for the Akidah Akhlak subject at MI Ma'arif NU 02 Karangpakis and third how is the evaluation of blended learning for the Akidah Akhlak subject at MI Ma'arif NU 02 Karangpakis. This research is a qualitative research because it produces qualitative data. Collecting data using interviews, observation and documentation. Test the validity of the data using triangulation techniques. Data analysis used description techniques with the Miles and Huberman interaction analysis model with flows including data collection, data reduction, data presentation and drawing conclusions. The results of the study concluded, firstly planning for blended learning in the Akidah Akhlak subject at MI Ma'arif NU 02 Karangpakis includes planning at the institutional level, namely preparing facilities and infrastructure to support blended learning and planning at the teacher level, namely setting material, setting goals, compiling a syllabus, prepare learning implementation plans, determine strategies, methods and media, determine learning activities, plan evaluations and determine follow-up steps, the second is the implementation of blended learning, namely the delivery of material by the teacher to students through a series of activities to teach students actively, creatively, productively and fun with apply various strategies and methods as well as the use of media and visual aids to achieve learning objectives and the three evaluations of belended learning include evaluations of the implementation of blended learning and evaluation of student learning outcomes